Tumors with Pilosebaceous Differentiation: A Five Year Retrospective Study at BPKIHS - Paudyal, P; Pradhan, A; Pokharel, S; Sah, N; Karki, S; Marhatta, S (Journal of Gandaki Medical College-Nepal, 2018)
Background: Skin appendageal tumors (SAT) are a large and diverse group of tumors that are commonly classified according to their state of appendageal differentiation: Follicular, sebaceous, eccrine and apocrine. Most adnexal neoplasms are uncommonly encountered in routine practice, and pathologists can easily recognise frequently encountered tumours. In this study, the histological features of important benign and malignant tumors of pilosebaceous origin were reviewed considering its morphologic types, subtypes, age, sex and anatomic site. Methods: This is a hospital based retrospective study which includes all cases of tumors with pilosebaceous differentiation diagnosed histologically during the period of five years (1st January, 2008 to 31st December, 2012). Tumors were analyzed considering the anatomic location and type of the tumor, along with age and sex of the patient. The Histological characterization was done according to the WHO classification system for SAT. Collected data were entered in Microsoft Excel 2000 and converted it into SPSS PC+ 11.5 Version for statistical analysis. Results: A total of 53 neoplasms of pilosebaceous differentiation included, 52 (98.1%) were benign and one (1.8%) was malignant. The mean age was 39.23 years. Females comprised of 35 (66%) and 18 (34%) were males. Most common location was in head and neck area. Of all, 51 (96.2%) tumors were follicular, and two (3.7%) were with sebaceous differentiation. Among all follicular tumors, Pilomatricoma (33.9%), Keratoacanthoma (26.4%) and Trichoepithelioma (22.6%) were the commonest tumors observed. Conclusion: The study findings reveal majority of the tumors origin were of follicular differentiation and all were benign. J-GMC-N | Volume 11 | Issue 01 | January-June 2018, Page: 33-39